Food : a dictionary of literal and nonliteral terms - Palmatier, Robert A. (Robert Allen) (Greenwood Press, 2000)
This dictionary explores the relationship between the literal and the nonliteral (idiomatic and metaphorical) language of the cooking and eating of food. Each entry contains a description of the historical background of each of the two types of language, and the works that record the terms.